Comparative Test of Midazolam Hydrochloride Stability in Different Storage and Temperature Container - Anang Endaryanto1 , Andang Miatmoko2 , Mela Dwi Wulandari3 , Novi Aryanti3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Midazolam hydrochloride is an injection form of benzodiazepines and included in the highalert category in the Dr. Soetomo Teaching Hospital Intensive Care Unit (ICU), Surabaya, Indonesia.Nowadays, the technical preparation of midazolam drugs in the ICU room by doctors and nurses wasperformed by reconstituting drugs in the injection syringes to be stored for a while in the room. Objectives:To evaluate the preparation process for midazolam hydrochloride injection which has been analyzed inDr. Soetomo Teaching Hospital. Methods: Physical, chemical, and microbiological stability of 1 mg/mLmidazolam hydrochloride in aqua pro injection solvents have been evaluated at points 0, 8, 12, and 24 hoursafter preparation, as well as a comparison of stability in storage conditions at room temperature comparedto refrigerator temperatures. Results: The results showed all the preparations were no foreign particlesin the sample container. The midazolam did not experience precipitation in both room and refrigeratortemperatures. The pH of midazolam solution during storage proved that the preparation was relatively stable(pH 4.3–4.5). There were no significant differences of midazolam levels in both storages which was in rangeof 95%. The Miccrobiology Stability Test showed negative germ growth after 24 hours incubation in bothstorage. Conclusion: This study showed no changes in physical, chemical, or microbiological stability in themidazolam injection samples up to 24 hours after the manufacturing process.